The experiences of a group of women soldiers serving in the South African National Defence Force. - Weiss Bar-Ner, Yael (My University, 1998)
This research report examines the experiences of a group of women-soldiers serving in the South African National Defence Force (SANDF) in relation to two major sociological concerns. The first concern is the South African transition and the establishment of the SANDF, and the second is gender issues within the military. There is little literature concerning women-soldiers in relation to the establishment of the SANDF. In addition, the iiterature on women and militarism suggests that there is no consensus amongst women around key questions regarding the military. Therefore, researching the experiences of'a group of women-soldiers required the use of research methods which would enable a free flow of information by the respondents. This particular group of research subjects was identified through the quota sampling technique. The group represented a large variety of social identities and backgrounds. The informants were interviewed primarily through structured in-depth interviews. The central finding of this research is that the informants had various experiences according to different sociological characteristics, such as race, previous military service, or marital status. In relation to the transition and the establishment of the SANDF, military experience and race were found to be the most important factors in shaping the respondents' experiences. In this regard, I have argued that the SANDF reflects the former SADF Concerning gender issues within the military, marital status appeared as the most relevant factor. Considering this, it is suggested that the social responsibilities attached to wifehood and motherhood influence women toward traditional female domains in the workplace.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Arts.
Keywords: Women soldiers -- South Africa.; South Africa. Army.